Types of Dictionaries in Kurdish Language - Nariman Abdullah Xoshnaw (QALAAI ZANIST JOURNAL, 2022)
1-Title of the study: Our research is entitled with (Types of Dictionary in Kurdish Language). 2-Limits of the study: The limit of the study is on practical linguistic level, the examples of the study covers Kurdish dictionaries in all dialects and accents, also contains these dictionaries that are between Kurdish and other languages. 3-Methods of the study: The method which is applied on this study is (descriptive analytical method). 4-Reasons of the study: Practical linguistic is an important branch of linguistics, discussing this science especially (dictionary and lexicology) has a close history, that is why although writing and researching is done, it is minimal so we chose this subject to enrich the Kurdish library. 5-Problems of the study: Unfortunately, the selection of dictionary types has not been shown in this extensive way as we applied in this study, but the sources have talked about them intermittently and incompletely, which has taken us a long time trying to show all kinds of dictionaries in Kurdish as an example of Kurdish dictionary. 6-Materials of the study: For this study, we have resorted to identifying the majority of Kurdish dictionaries, especially those published in regular books or electronic books. 7-Research content and research plan: The study consists of an introduction and two chapters: Chapter One: which is titled (dictionary), contains these sections: (term and definition of dictionary, dictionary term, dictionary definition, dictionary benefits, basic dictionary letters order). Chapter Two: which is titled (dictionary types), contains these sections: (dictionary types in terms of features, dictionary types in terms of content, dictionary types in terms of size, dictionary types in terms of style, dictionary types in terms of language numbers, dictionary types in terms of quantity, dictionary types in terms of subjectivity). Finally, the results of the study and the list of references, with the abstract of the study presented in Arabic and Englishز